Thermally stable floor and preparation method thereof

通过在PETG树脂中加入PC树脂和其他改性剂,解决了PETG地板在温度变化时尺寸不稳定的问题,实现了更高的热稳定性和机械性能,同时改善了加工性能和表面质量。

CN119432021APending Publication Date: 2025-02-14CHANGZHOU BEMATE HOME TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411809194.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

PETG floors are prone to thermal expansion and contraction when temperature changes, resulting in dimensional instability, warping or gap problems.

Method used

Add PC resin to PETG resin and use toughening polymers, inorganic fillers, antioxidants, lubricants and modifiers, such as DEG, to improve the thermal stability and processing properties of the material.

Benefits of technology

By enhancing the binding force between the molecular chains and increasing the glass transition temperature, the thermal stability and mechanical properties of PETG floors are significantly improved, dimensional instability and warping problems are reduced, while improving processability and surface quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432021A_ABST
    Figure CN119432021A_ABST
Patent Text Reader

Abstract

The invention relates to a stable floor and a preparation method thereof, and the heat stable floor comprises the following components in parts by mass: 60-70 parts of PETG resin; 10 to 30 parts of PC resin; 1-10 parts of a toughening polymer; 250 to 300 parts of an inorganic filler; 0.1 to 0.5 part of an antioxidant; 0.1 to 0.5 part of a lubricant; and 1-2 parts of a modifier. The PC resin, the toughening polymer, the inorganic filler, the antioxidant, the lubricant and the modifier are added into the PETG resin to prepare the heat-stable floor, the PETG resin is modified, and all the substances have a synergistic effect, so that the heat-stable PETG floor not only has excellent mechanical properties and heat properties, but also has excellent mechanical properties and heat resistance. Good processability and long-time use stability are also realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of flooring, in particular to a heat-stable flooring and a preparation method thereof. Background Art

[0002] Among traditional floor materials, PVC (Polyvinylchloride) flooring has been widely used due to its low cost and good durability.

[0003] However, PVC flooring has significant environmental problems. A large amount of chlorine compounds are used in the production process of PVC flooring, which may release harmful gases and volatile organic compounds (VOCs), affecting indoor air quality and posing potential risks to health. In addition, PVC flooring is difficult to recycle and reuse efficiently after its service life ends, which increases the environmental burden.

[0004] PETG (Polyethylene Terephthalate Glycol-modified) is a new type of floor material. PETG is a thermoplastic synthesized from terephthalic acid (PET) and ethylene glycol (EG). Chlorides are not used in its production process, and PETG flooring does not release harmful volatile organic compounds (VOC) during production and use, which meets environmental protection requirements. In addition, PETG flooring also has excellent mechanical properties, is easier to be recycled and reused, has better anti-bacterial properties, and better transparency.

[0005] However, due to the low thermal stability of PETG, the solution undergoes thermal expansion and contraction when the temperature changes, which may cause dimensional instability, warping or gap problems when PETG is used in flooring applications. Summary of the invention

[0006] Based on this, it is necessary to provide a heat-stable floor and a preparation method thereof, aiming to solve the technical difficulties in the prior art of applying PETG in the field of flooring, such as dimensional instability, warping or gap problems.

[0007] To achieve the above object, the present invention provides a technical solution:

[0008] A heat-stable floor, measured by mass, comprising:

[0009] PETG resin 60-70 parts;

[0010]

[0011] PETG is an ester polymer formed by copolymerization of terephthalic acid and ethylene glycol. Its main chain contains a large number of ester bonds, which are prone to hydrolysis or thermal degradation reactions at high temperatures. PETG also has a low glass transition temperature (Tg), a flexible molecular chain structure, a lack of structural units that enhance thermal stability, and is sensitive to thermal oxidation and moisture. These factors work together to make PETG prone to degradation, deformation, and performance degradation in high-temperature environments, which leads to PETG's easy thermal expansion and contraction when the temperature changes. When it is used in the field of flooring, there are technical difficulties such as dimensional instability, warping, or gap problems.

[0012] The present invention adds PC resin to PETG resin, which has a significant effect on the thermal stability of PETG resin, and this effect is mainly achieved through the interaction between materials:

[0013] 1. PC molecules contain carbonyl (C=O) and hydroxyl (OH), which can form hydrogen bonds with ester groups (C=O) in PETG. The presence of hydrogen bonds can enhance the interaction between PETG resin and PC resin, increase the binding force between molecular chains, and thus improve the thermal stability of the mixed material.

[0014] 2. The glass transition temperature (Tg) of PC is much higher than that of PETG. Through blending, PC can increase the Tg of the entire system, thereby delaying the softening and deformation of PETG at high temperatures. This means that the mixed material of PETG resin and PC resin can still maintain good mechanical properties and dimensional stability at higher temperatures.

[0015] 3. When PETG resin begins to pyrolyze, PC can absorb and passivate the degradation products to prevent them from further initiating the degradation reaction of PETG resin. Through this passivation effect, PC resin helps stabilize the thermal decomposition process of PETG resin.

[0016] 4. PC resin (Polycarbonate) has a higher heat deformation temperature (usually above 120°C), which is much higher than the heat deformation temperature of PETG (about 75°C). After adding PC resin, the overall heat deformation temperature of the mixed material is increased, which enhances the dimensional stability of the material under high temperature conditions.

[0017] However, due to the high melt viscosity of PC resin, the fluidity deteriorates during processing, affecting the extrusion and molding effects. That is, due to the poor melt fluidity of PC / PETG, flow marks and signs of insufficient stretching are easily produced, resulting in defects in the molding of floor samples and a high floor molding loss rate.

[0018] The present invention improves fluidity by adding a modifier DEG (diethylene glycol), and the interaction between DEG and PC / PETG chain segments reduces the melt viscosity of PC / PETG, improves fluidity, and improves processing performance.

[0019] On the other hand, inorganic fillers are added, which are combined with the organic matrix of PC / PETG and filled in the polymer matrix to improve the rigidity and dimensional stability of the composite material and reduce the thermal expansion coefficient. In some embodiments, the inorganic filler includes at least one of calcium carbonate, clay, kaolin and talc.

[0020] Further, the antioxidant plays a key protective role in the PC / PETG mixture, preventing oxidative degradation during high temperature processing and maintaining the mechanical strength and optical properties of the material. It forms a relatively stable chemical environment with the polymer matrix, thereby extending the service life of the material. In certain embodiments, the antioxidant includes at least one of antioxidant 1010, antioxidant 168, antioxidant 1076, antioxidant CA, antioxidant TPP, antioxidant DLTP and antioxidant TNP.

[0021] Furthermore, the lubricant improves the processing fluidity of the material by reducing the friction between PC, PETG and the inorganic filler, thereby making the composite material smoother during extrusion and molding, reducing mold wear and improving surface quality. In some embodiments, the lubricant includes at least one of calcium stearate, zinc stearate, magnesium stearate, PE wax and PETS.

[0022] Furthermore, the toughening polymer includes methyl acrylate-ethyl methacrylate copolymer (PolyMethylMethacrylate-EthylMethacrylate, PMMA-EMA), and PMMA-EMA has good compatibility with PETG resin and PC resin respectively. When PMMA-EMA is mixed with PC / PETG, due to the good compatibility, it can be evenly dispersed at the molecular level to form a continuous phase structure. This uniform phase distribution helps to effectively transfer stress, thereby significantly improving the toughness and impact resistance of the material.

[0023] In addition, because PMMA-EMA can form a uniform phase structure in the blended material and reduce the scattering of light, PMMA-EMA has good transparency and will not significantly affect the transparency of the PC / PETG blended material after addition.

[0024] EMA is a special copolymer of ethylene and methyl acrylate, with high elasticity, excellent resistance to bending cracking and environmental stress cracking, good low temperature performance and softness, and high filler holding capacity. Its rubber-like properties make it suitable for low melting point products of hot melt adhesives, and its polyethylene-like properties make it suitable for producing products with extraordinary toughness and flexibility, and its application range is very wide. It has the following characteristics:

[0025] 1. Excellent thermal stability, cold resistance, weather resistance, and aging resistance;

[0026] 2. Excellent coloring and filling properties, good dimensional stability, widely used in packaging, medical devices, profiles, etc.;

[0027] 3. It has excellent flexibility and elasticity, is used for plastic modification, and has good resistance to environmental stress cracking;

[0028] 4. It contains polar and non-polar functional groups, has excellent compatibility with polymers, can be used as a compatibilizer, and can be welded at high frequency;

[0029] 5. It has outstanding bonding properties and improves bonding strength;

[0030] 6. It has excellent sealing and tearing properties and low-temperature heat sealing properties, suitable for food packaging, medical packaging, etc.

[0031] The preparation steps of PMMA-EMA are as follows:

[0032] S100, methyl acrylate, can be obtained by esterification of acrylic acid and methanol, or by reaction of cyanoethanol and methanol in the presence of concentrated sulfuric acid

[0033] S200, add methacrylic acid and anhydrous ethanol into the reaction pot, add a small amount of concentrated sulfuric acid, heat and reflux until the ester layer appears. Cool, separate the ester layer, wash with alkali, wash with water, dry, and then reduce the pressure to fractionate to obtain the product. The industrial product ethyl methacrylate content is ≥98%. Raw material consumption quota: methacrylic acid 950kg / t, ethanol 900kg / t.

[0034] S300, using a suspension copolymerization method to prepare a methyl acrylate-ethyl methacrylate copolymer by using the methyl acrylate and ethyl methacrylate prepared above (which can also be purchased)

[0035] Furthermore, the molecular weight of the PC resin is 24,000 to 30,000. When the molecular weight increases:

[0036] Improved tensile strength: PC resin is more able to withstand tensile forces and less likely to break.

[0037] Improved impact resistance: helps resist external impact and reduces the possibility of breakage.

[0038] Slightly improved heat resistance: performance can remain stable at higher temperatures.

[0039] Good fatigue properties: better resistance to cyclic stress cycles.

[0040] Improved creep rupture strength: Less susceptible to creep rupture under long-term loads.

[0041] Improved chemical resistance: More resistant to attack by chemicals.

[0042] Improved blow moldability: Easier to process by blow molding.

[0043] Improved extrudability: performs better during extrusion.

[0044] However, the larger the molecular weight is, the better it is not, because when the molecular weight reaches an extreme value, the impact resistance may tend to remain the same or decrease (ultra-high molecular weight is not considered here).

[0045] As the molecular weight decreases:

[0046] Good fluidity in the mold makes it easier to fill the mold.

[0047] Good mixing properties in the barrel.

[0048] The cooling and solidification speed in the mold is faster.

[0049] Slightly increased rigidity.

[0050] Furthermore, the size of the inorganic filler is 400-600 mesh.

[0051] More specifically, the mesh size of calcium carbonate has a significant impact on the performance and appearance of the floor. The larger the mesh size, the finer the calcium carbonate particles, and its effect on the floor material is also different. Here are some specific effects of mesh size on flooring:

[0052] 1. Surface finish

[0053] High mesh count (fine particles):

[0054] High-mesh calcium carbonate particles are finer, usually 400 mesh or above. When fine-particle calcium carbonate is filled in floor materials, it can improve the smoothness and fineness of the floor surface and reduce surface defects such as tiny pits and depressions. Therefore, using high-mesh calcium carbonate helps to obtain a floor with a smoother surface and better touch.

[0055] Low mesh (coarse particles):

[0056] The particles of low-mesh calcium carbonate are larger, usually below 400 mesh. Coarse particles of calcium carbonate may cause obvious graininess and roughness on the surface of the floor, affecting the appearance and feel of the floor.

[0057] 2. Material strength

[0058] High mesh count (fine particles):

[0059] High-mesh calcium carbonate can be dispersed more evenly in the matrix material due to its fine particles, which helps to improve the cohesion of the floor and the uniformity of the material. This can enhance the tensile strength and bending resistance of the floor, while reducing the internal stress concentration of the material.

[0060] Low mesh (coarse particles):

[0061] Low-mesh calcium carbonate may form stress concentration points in the material, especially when the floor is under stress, these coarse particles may become the starting points of cracks, reducing the tensile strength and impact resistance of the material.

[0062] 3. Wear resistance of the floor

[0063] High mesh count (fine particles):

[0064] Because fine particles of calcium carbonate can be evenly distributed in the matrix, it helps to improve the wear resistance of the floor and reduce the phenomenon of particle shedding during wear. The floor will show better wear resistance during use.

[0065] Low mesh (coarse particles):

[0066] Calcium carbonate particles with low mesh count are larger and can be easily pulled out during wear, causing pits or irregular wear on the floor surface, thereby reducing wear resistance.

[0067] 4. Density and weight of the floor

[0068] High mesh count (fine particles):

[0069] High mesh count calcium carbonate fillers can be more evenly and densely distributed in the base material, resulting in an increase in the overall density of the material. This may increase the weight of the floor, while also increasing the compressive strength and hardness of the material.

[0070] Low mesh (coarse particles):

[0071] Coarse particles of calcium carbonate have a lower filling efficiency and the overall density of the material may be slightly lower, resulting in a relatively light floor. However, this low density may affect the hardness and durability of the floor.

[0072] 5. Transparency and appearance

[0073] High mesh count (fine particles):

[0074] If the floor material needs to maintain a certain degree of transparency, using high-mesh fine-grained calcium carbonate can help reduce light scattering and maintain the transparency and gloss of the material. This is very important for floors with certain special appearance effects.

[0075] Low mesh (coarse particles):

[0076] Calcium carbonate particles with low mesh counts are larger and tend to form light scattering points, which reduces the transparency of the flooring material and makes the appearance uneven. The surface may appear rough and uneven.

[0077] Although too high a mesh count of calcium carbonate can bring some advantages, such as improving surface finish and transparency, it may also bring some potential negative effects, mainly in terms of processability, material properties, cost, etc. The following are the possible effects of too high a mesh count:

[0078] 1. Processability

[0079] Difficulty in dispersion: The higher the mesh number, the finer the calcium carbonate particles, which makes it more difficult to disperse in the polymer matrix. Fine particles tend to agglomerate and form lumps, resulting in uneven distribution in the material, thus affecting the overall performance of the floor.

[0080] Increased mixing difficulty: Due to the large surface area of ​​high-mesh calcium carbonate particles, stronger mixing force and longer mixing time may be required to ensure uniform dispersion. This will increase the load and energy consumption of processing equipment and affect production efficiency.

[0081] 2. Material properties

[0082] Plasticizing effect: Calcium carbonate particles with too high a mesh count may have a similar effect to plasticizers on the base material due to their fine particles. This may lead to a decrease in the modulus and softening point of the material, thus affecting the mechanical strength and heat resistance of the floor.

[0083] Reduced material hardness: Too fine calcium carbonate particles may cause the hardness of the floor material to decrease, especially when the filling amount is high. This is because the high-mesh calcium carbonate particles are relatively soft and cannot increase the rigidity and hardness of the material as much as the coarser particles.

[0084] 3. Increased costs

[0085] Production cost: The production process of high-mesh calcium carbonate is complicated and requires a more delicate crushing and screening process, so the production cost is higher. If a large amount of high-mesh calcium carbonate is required in the floor formula, the cost of raw materials may increase significantly.

[0086] Processing cost: Since high-mesh calcium carbonate causes greater wear on equipment, more wear-resistant equipment or more frequent equipment maintenance may be required during the processing, thereby increasing production costs.

[0087] 4. Potential interface issues

[0088] Interfacial compatibility: The surface area of ​​high-mesh calcium carbonate particles increases, which increases the interfacial area between the particles and the polymer matrix. If the interfacial compatibility is insufficient, micropores or microcracks may form at the interface, affecting the overall performance of the material.

[0089] Wettability requirements: Due to its large surface area, high-mesh calcium carbonate requires better wettability and dispersants to ensure good bonding with the polymer matrix. If the wetting is insufficient, it may lead to poor interface bonding, affecting the mechanical properties and durability of the material.

[0090] 5. Wear of processing equipment

[0091] Equipment wear: Although calcium carbonate particles with too high a mesh size are small, their high surface area and quantity may accelerate the wear of processing equipment (such as extruders, mixers, etc.). This will shorten the service life of the equipment and increase the cost of maintenance and replacement of equipment.

[0092] The present invention also provides a method for preparing a heat-stable floor, comprising the steps of:

[0093] PETG resin, PC resin, toughening polymer, inorganic filler, antioxidant, lubricant and modifier are stirred and heated to 110° C. to 120° C. to obtain a mixture;

[0094] The mixed material is cooled, extruded and formed, attached to a wear-resistant layer, embossed and then cut to obtain the heat-stable floor.

[0095] Furthermore, the extrusion molding is carried out through a conical twin-screw extruder, wherein the barrel temperature of the conical twin-screw extruder is controlled at 160°C to 180°C, the mold temperature of the conical twin-screw extruder is controlled at 200°C to 220°C, and the die cooling temperature of the conical twin-screw extruder is controlled at 100°C to 140°C.

[0096] Beneficial effects of the present invention:

[0097] The invention prepares a heat-stable floor by adding PC resin, toughening polymer, inorganic filler, antioxidant, lubricant and modifier into PETG resin, and modifies the PETG resin. The synergistic effect between various substances makes the heat-stable PETG floor not only excellent in mechanical properties and thermal properties, but also good in processability and stability for long-term use. BRIEF DESCRIPTION OF THE DRAWINGS

[0098] Figure 1 Flow curves of PETG copolyesters with different DEG contents at 270°C. DETAILED DESCRIPTION

[0099] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0100] In the examples, the test methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.

[0101] 1. Set up examples and comparative examples, and compare them with conventional floors.

[0102] 1. Flooring formulations of the embodiments and comparative examples: The flooring formulations of the embodiments and comparative examples are shown in Table 1 in parts by mass.

[0103] Table 1 Flooring formula table of each embodiment and comparative example

[0104]

[0105]

[0106] Among them, the selected PETG resin has a molecular weight of about 100,000-150,000, because the larger the molecular weight, the worse the fluidity will be, which will affect the molding of the material, and the mass ratio of diol 1,4-cyclohexanedimethanol and ethylene glycol in the PETG resin is 5:5.

[0107] Calcium carbonate powder is 400 mesh.

[0108] The toughening polymer used is methyl acrylate-ethyl methacrylate copolymer, and its preparation steps are as follows:

[0109] S100, methyl acrylate, can be obtained by esterification of acrylic acid and methanol, or by reaction of cyanoethanol and methanol in the presence of concentrated sulfuric acid.

[0110] S200, add methacrylic acid and anhydrous ethanol into the reaction pot, add a small amount of concentrated sulfuric acid, heat and reflux until the ester layer appears. Cool, separate the ester layer, wash with alkali, wash with water, dry, and then reduce the pressure to fractionate to obtain the product. The industrial product ethyl methacrylate content is ≥98%. Raw material consumption quota: methacrylic acid 950kg / t, ethanol 900kg / t.

[0111] S300, adopting suspension copolymerization method to prepare methyl acrylate-ethyl methacrylate copolymer by suspension copolymerization of methyl acrylate and ethyl methacrylate prepared as above (which can also be purchased), wherein the mass ratio of methyl acrylate to ethyl methacrylate is 1:1.

[0112] 2. Floor preparation process of the embodiment and comparative example:

[0113] PETG resin, PC resin, toughening polymer, inorganic filler, antioxidant, lubricant and modifier are stirred and heated to 110° C. to 120° C. to obtain a mixture;

[0114] The mixed material is cooled to 65° C. and placed in a storage bin, and the mixed material in the storage bin is transported to a twin-screw extruder (a conical twin-screw extruder) through a spiral feeding system.

[0115] The barrel temperature is controlled at 160℃~180℃, the mold temperature is controlled at 200-220℃, the die cooling temperature is controlled at 100-140℃, and after extrusion, it is formed by the mold, and the thickness is adjusted and shaped by rollers 1 and 2. The wear-resistant layer (PETG material) is preheated / pressed at the position of roller 3; rollers 4 and 5 are used for embossing, and the sheet is cut after cooling.

[0116] 3. Preparation of conventional floor 1

[0117] 1) Formula of conventional floor 1: Its base material components are 90 parts of PVC resin powder, 297 parts of 400 mesh calcium carbonate, 80 parts of recycled materials, 5.8 parts of calcium zinc stabilizer, 0.7 parts of external lubricating PE wax, and 1.7 parts of internal lubricating CA80, where recycled materials refer to the scraps of PVC resin and calcium carbonate floor in the formula.

[0118] 2) Conventional floor 1 extrusion process, its characteristics and backing film selection include the following steps:

[0119] Add calcium carbonate, PVC powder and part of the recycled material into a high-speed mixer, then add plasticizer, stabilizer and lubricant, mix and stir, heat to 110-120°C, then cool and obtain a mixture.

[0120] When the mixed material is cooled to 65°C, it is placed in a storage bin, and the mixed material in the storage bin is transported to a twin-screw extruder (a conical twin-screw extruder) through a spiral feeding system.

[0121] The barrel temperature is controlled at 160-180℃, the mold temperature is controlled at 200-220℃, the die cooling temperature is controlled at 100-140℃, after extrusion, it is formed by the mold, and the thickness is adjusted and shaped by rollers 1 and 2. Roller 3 is used to laminate the color film and wear-resistant layer, and rollers 4 and 5 are used for embossing. After cooling, it is cut to obtain a conventional floor.

[0122] 4. Preparation of conventional floor 2

[0123] 1) Formula of conventional floor 2: 75 parts of PVC resin powder, 250 parts of heavy calcium carbonate, 80 parts of recycled materials, 6.8 parts of calcium zinc stabilizer, 1.5 parts of external lubricating PE wax, 1.2 parts of internal lubricating CA80, where recycled materials refer to the scraps of PVC resin and calcium carbonate floor in the formula.

[0124] 2) The extrusion process of conventional floor 1 is the same as the extrusion process of conventional floor 2.

[0125] The parameters of the conical twin-screw extruder in the extrusion process of the flooring obtained in the embodiment and the comparative example and the conventional flooring 1 and the conventional flooring 2 are as follows in Table 2.

[0126] Table 2 Extruder parameters

[0127]

[0128]

[0129] The floors prepared in the examples and comparative examples, as well as conventional floor 1 and conventional floor 2 were subjected to performance tests, and the results are shown in Table 3.

[0130] Table 3 Performance test results

[0131]

[0132] Among them, due to the lack of important components in Comparative Examples 1, 4 and 6, the implementation could not be completed.

[0133] As can be seen from Table 3, in the embodiment, PC resin, toughening polymer, inorganic filler, antioxidant, lubricant and modifier are added to PETG resin to prepare a heat-stable floor. The PETG resin is modified, and the synergistic effect between the substances makes the heat-stable PETG floor not only excellent in mechanical properties and thermal properties.

[0134] 2. Explore the impact of DEG content in floor

[0135] The effect of changes in DEG content in the floor on the floor substrate is shown in Table 4.

[0136] Table 4 Effect of changes in DEG content on floor substrates

[0137]

[0138] It can be seen from Table 4 that with the increase of DEG content, the performance of the seven slices is not significantly improved, so 1 portion can be selected as the addition amount.

[0139] 3. The flow curves of PETG copolyesters with different DEG contents at 270°C are as follows Figure 1 shown.

[0140] Equipment: capillary rheometer.

[0141] Depend on Figure 1 It can be seen that at the same shear rate, with the increase of DEG content, the shear viscosity gradually decreases.

[0142] It should be noted that the specific parameters or some reagents in the above embodiments are specific embodiments or preferred embodiments of the present invention, rather than limiting the present invention; those skilled in the art can make adaptive adjustments within the scope of the present invention.

Claims

1. A thermally stable floor, characterized in that: The heat-stable floor comprises, by mass:

2. The heat-stable floor according to claim 1, characterized in that: The toughening polymer includes methyl acrylate-ethyl methacrylate copolymer.

3. The thermally stable floor according to claim 1, characterized in that: The molecular weight of the PC resin is 24,000 to 30,000.

4. The thermally stable floor according to claim 1, characterized in that: The inorganic filler includes at least one of calcium carbonate, clay, kaolin and talc.

5. The thermally stable floor according to claim 1, characterized in that: The size of the inorganic filler is 400-600 meshes.

6. The thermally stable floor according to claim 1, characterized in that: The antioxidant includes at least one of antioxidant 1010, antioxidant 168, antioxidant 1076, antioxidant CA, antioxidant TPP, antioxidant DLTP and antioxidant TNP.

7. The thermally stable floor according to claim 1, characterized in that: The lubricant includes at least one of calcium stearate, zinc stearate, magnesium stearate, PE wax and PETS.

8. The thermally stable floor according to claim 1, characterized in that: The modifier includes DEG.

9. A method for preparing a heat-stable floor as claimed in any one of claims 1 to 8, characterized in that: Includes steps: PETG resin, PC resin, toughening polymer, inorganic filler, antioxidant, lubricant and modifier are stirred and heated to 110° C. to 120° C. to obtain a mixture; The mixed material is cooled, extruded and formed, attached to a wear-resistant layer, embossed and then cut to obtain the heat-stable floor.

10. The preparation method according to claim 9, characterized in that: The extrusion molding is carried out through a conical twin-screw extruder, wherein the temperature of the barrel of the conical twin-screw extruder is controlled at 160°C to 180°C, the temperature of the mold of the conical twin-screw extruder is controlled at 200°C to 220°C, and the die cooling temperature of the conical twin-screw extruder is controlled at 100°C to 140°C.

Citation Information

Cited By

  • High-strength heat-resistant flame-retardant floor base material based on regenerated PETG (polyethylene terephthalate glycol) and preparation method thereof

    CN121293699A